Teachers’ Perspective towards Using the "Lets View" Application as Innovative Learning Media for Elementary Students in English Foreign Language Classroom - Wardani, Andini Dwi; Munir, Ahmad (JTP - Jurnal Teknologi Pendidikan, 2023)
The advancement of technology has a significant impact on teaching English nowadays. One of the tools that can quickly provide access to language learning is a mobile device. Moreover, the rising use of mobile devices or Mobile Assisted Language Learning (MALL) has been closely linked to the role of EFL teachers. Hence, this study aimed to investigate teachers’ perspectives towards using the "Lets View" application for elementary students in the EFL classroom. The study was conducted by implementing a qualitative method. The instrument used in this study was questionnaires and interviews. The subject of this study was six English elementary school teachers who teach using the LV application in a private school in Surabaya. The results showed that using the new learning media, such as the LV application in EFL classrooms, is very useful for teachers. It is due to that this application can use mobile phones or iPad as the second portable blackboard for teaching reading, writing, and vocabulary and giving quizzes for beginner-level students. The researchers also revealed four obstacles EFL teachers face when implementing the LV application: internet connection, time limitation, lack of teachers’ competence, and lack of student’s English skills. Besides, several ways to increase students’ learning engagement include allowing students to raise their hands, playing the game on the application, and guessing English vocabulary by giving pictures that appeared on it. To sum up, teachers viewed the LV application as suitable media for learning English at school.